Символіко-алегоричний концептуалізм Т. Шевченка: інтроспективна серія «Телемах - Діоген» - Генералюк, Л. (Студії мистецтвознавчі, 2009)
The article is dedicated to the problem in culture and mutual influence of different kind of arts in the middle of the 19th century. Creativity of the poet and artist T. Shevchenko shows separate aspects of interactions of literature and art. Here is brought to your attention a new interpretation of Shevchenko’s graphic series «The Telemach – Diogen» (1856). Article opposes the Soviet and modern Shevchenko critics according to whom this series wrongfully name as «The Suite of the Loneliness», and which represent Shevchenko as the depressive lonely revolutionary rebel. Author of this article considers that images of series «The Telemach – Diogen» which according to tradition of academism have analogies in the Bible, antique history, mythology and the literature visualise an introspective line of spiritual searches of Shevchenko. The central theme is theme to self-knowledge, self-comprehension of the person. In each of ten single sheets of a series the artist makes the psychological analyses of various embodiments of own deep «I» – of Person, of Anima etс. Most of all Shevchenko excites a question of preservation of shape of the God at the person who has passed difficult vital tests. As a whole a series is a philosophical parable about the statement of strength of spirit of the person creativity, operating, conceiving. It is optimistically and aimed at actualisation of internal personal freedom, freedom of choice.